Integrated Learning Management During Pandemic - Abdullah Abdullah; M Omar (Journal of Research in Educational Management, 2022)
During the COVID-19 pandemic, educational institutions, including madrasas and schools, faced significant challenges in maintaining the continuity and quality of learning processes due to restrictions on face-to-face interactions. The sudden transition from conventional classroom-based learning to online learning required schools to adapt rapidly by utilizing digital technologies and developing innovative learning models. However, the implementation of fully online learning also encountered various obstacles, such as limited digital competence among teachers, unequal access to technology, student engagement issues, and difficulties in monitoring learning outcomes. Therefore, educational institutions need a flexible learning approach that combines the advantages of face-to-face and online learning. This study employed a qualitative research approach using a descriptive method to explore the implementation of Hybrid Learning management in madrasas/schools during the COVID-19 pandemic. Data were collected through observation, interviews, and documentation related to learning management practices, curriculum planning, learning implementation, and evaluation processes. The participants consisted of school principals, teachers, and relevant educational staff involved in implementing Hybrid Learning. The results showed that at the planning stage, schools formulated a unique curriculum adapted to the Hybrid Learning learning model during the Covid-19 Pandemic and supported by adequate learning facilities and infrastructure. At the implementation stage, there is a slight difference between theory and accurate data regarding offline and online learning time. Implementing a shift system, one week of offline learning and another week of online learning. Meanwhile, online/online learning is tailored to the needs of each teacher. Schools carry out face-to-face/offline and online/web-based evaluations at the evaluation stage.